ATM priming and end resection–coupled phosphorylation of MRE11 is important for fork protection and replication restart - Huimin Zhang; Youhang Li; Sameer Bikram Shah; Shibo Li; Qingrong Li; Joshua Oaks; Tinghong Lv; Linda Z. Shi; Hailong Wang; Dong Wang; Xiaohua Wu (Proceedings of the National Academy of Sciences, 2025)
The MRE11/RAD50/NBS1 (MRN) complex plays multiple roles in the maintenance of genome stability. MRN is associated with replication forks to preserve fork integrity and is also required for end resection at double-strand breaks (DSBs) to facilitate homologous recombination (HR). The critical need for proper control of the MRE11 nuclease activity is highlighted by the extensive nascent strand DNA degradation driven by MRE11 in BRCA-deficient cells, leading to genome instability and increased sensitivity to chemotherapeutics. In this study, we identified a tightly controlled mechanism, elicited by sequential phosphorylation of MRE11 by ATM and ATR to regulate MRE11 nuclease activities through its DNA binding. Specifically, at DSBs, MRE11 phosphorylation by ATM at the C-terminal S676/S678 primes it for subsequent phosphorylation by ATR, whose activation is triggered by end resection which requires the MRE11 nuclease activity. This ATR-mediated phosphorylation in turn induces MRE11 dissociation from DNA, providing a feedback mechanism to regulate the extent of end resection. At stalled replication forks, however, without ATM priming, MRN is stably associated with forks despite ATR activation. Furthermore, the ATR phosphorylation–defective MRE11 mutants are retained at single-ended DSBs formed by fork reversal upon replication stress, leading to extensive degradation of nascent DNA strands. Importantly, this end resection–coupled MRE11 phosphorylation elicits another critical layer of fork protection of nascent DNA in addition to BRCA2, ensuring proper end resection that is sufficient for replication restart at reversed forks while maintaining fork stability.